2016
DOI: 10.1590/s0004-28032016000200003
|View full text |Cite
|
Sign up to set email alerts
|

Her2 Expression as a Prognostic Factor in Metastatic Gastric Cancer

Abstract: -Background -Human epidermal growth factor receptor 2 (EGFR2/HER2/ErbB2) is a transmembrane receptor that stimulates cell proliferation when activated. The correlation of HER2 expression with prognosis has been studied in many cancer types. However, its relationship with survival of patients with metastatic gastric cancer remains unknown. Moreover, there is a lack of information on this issue in a Brazilian population. Objective -To assess the proportion of patients whose tumor cells express HER2 and correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…HER-2 overexpression or amplification has been associated with a more aggressive disease, a poor clinical prognosis. 23,24 Our study showed that elevated serum HER-2 ECD could be associated to a more aggressive clinical course. There are several explanations for the link between HER-2 ECD level and PFS.…”
Section: Discussionmentioning
confidence: 69%
“…HER-2 overexpression or amplification has been associated with a more aggressive disease, a poor clinical prognosis. 23,24 Our study showed that elevated serum HER-2 ECD could be associated to a more aggressive clinical course. There are several explanations for the link between HER-2 ECD level and PFS.…”
Section: Discussionmentioning
confidence: 69%
“…Fornaro et al (2011) reported that intestinal-type gastric cancers show more HER-2 positivity compared to diffuse-type gastric cancers. In their study, Junior et al (2016) reported that HER-2 overexpression was a poor prognostic factor in metastatic gastric cancer patients. In their meta-analysis study, Lei et al (2017) stated that genetic and geographic factors were effective in HER-2 expression, and HER-2 positivity was associated with gender, TNM stage, distant organ metastasis, lymph node metastasis, and Lauren classification.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of gastric cancer are adenocarcinomas (3,4); the main risk factors of gastric adenocarcinoma are age >60 years (3,5), male gender (5-7), low socioeconomic status, occupational exposure (high temperatures and dust, asbestos, X and gamma radiation, inhalation of hexavalent chromium, and inorganic lead compounds) (8), smoking, alcohol consumption, obesity, gastroesophageal reflux disease, Helicobacter pylori infection, high consumption of salt and nitrites, and low consumption of fresh fruit and vegetables (3,4,9). Prognostic factors include the presence of comorbidities (10, 11), smoking, alcohol consumption (12), clinical stage (13-15), and clinical and molecular characteristics of the tumors (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%